2017
DOI: 10.1007/978-3-319-57613-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells

Abstract: Endothelial cells are a constitutive part of the heart and vasculature and form a crucial link between the cardiovascular system and the immune system. Besides their commonly accepted roles in angiogenesis, hemostasis, and the regulation of vascular tone, they are an essential and active component of immune responses. Expression of a range of innate pattern recognition receptors allows them to respond to inflammatory stimulation, and they control immune cell recruitment and extravasation into target tissues th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(152 citation statements)
references
References 111 publications
1
144
0
7
Order By: Relevance
“…28 However, when vascular endothelial cells are exposed to an external stimulus, their structure and function become impaired, leading to large accumulations of lipids in blood vessels and changes in vascular permeability. 29 At the same time, these changes promote the proliferation of vascular smooth muscle cells, resulting in thrombus formation and platelet adhesion, and ultimately, the formation of atherosclerotic plaque. 30,31 In our study, we used ox-LDL-treated endothelial cells as a model in which to investigate the pathogenesis of atherosclerotic disease, and found that ox-LDLs could inhibit cholesterol efflux, and downregulate ABCA1 and ABCG1 expression in a dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, when vascular endothelial cells are exposed to an external stimulus, their structure and function become impaired, leading to large accumulations of lipids in blood vessels and changes in vascular permeability. 29 At the same time, these changes promote the proliferation of vascular smooth muscle cells, resulting in thrombus formation and platelet adhesion, and ultimately, the formation of atherosclerotic plaque. 30,31 In our study, we used ox-LDL-treated endothelial cells as a model in which to investigate the pathogenesis of atherosclerotic disease, and found that ox-LDLs could inhibit cholesterol efflux, and downregulate ABCA1 and ABCG1 expression in a dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…ECs are the basis for the formation of the inner surface of blood vessels. 416 Studies reported that glioblastoma stem cells are located around the blood vessels, and the concept of the cancer microvascular environment was first proposed. Calabrese et al 417 demonstrated that direct contact between ECs and CSCs occurs in brain tumors.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…In contrast to cardiomyocytes, endothelial injury may affect cardiac function by mechanisms other than the death of endothelial cells, including increased permeability and edema, and recruitment of platelets and inflammatory cells [407]. …”
Section: Cell Types Other Than Cardiomyocytesmentioning
confidence: 99%